Eccentricity of Acute Myeloid Leukemia with NPM1 and FLT3-ITD mutation: a case report - Nur Zainura Mohamad,; Alia Suzana Asri,; Salwati Shuib,; Nor Rafeah Tumian,; Suria A., (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Acute myeloid leukaemia (AML) is the most prevalent type of acute leukaemia in adults, with a heterogenous cytogenetics landscapes. NPM1 mutated AML was designated as a provisional entity in 2008 World Health Organisation (WHO) Classification of Tumours of Haematopoietic and Lymphoid Tissues. In 2017, fourth edition was revised and AML was recognised as a distinct entity with distinctive cytological, molecular and clinicopathological features. For example, AML with NPM1 mutation is strongly associated with acute myelomonocytic and acute monocytic leukemia. In recent studies, AML with both NPM1 and FLT3- ITD mutations, had been associated of blasts with cup-like nuclei. We described this characteristical morphology in a 68-year-old female who was diagnosed with AML alongside NPM1 and FLT3-ITD mutation. She presented with a short history of fever and laboratory findings of hyperleukocytosis, mild anemia and thrombocytopenia. A diagnosis of AML was proposed from the cytological and flow cytometry examinations. The full blood picture and bone marrow aspirate showed some of the blasts with cup-like nuclei and the flow cytometry examination showed characteristical feature which was suggestive of AML with NPM1 mutation. Polymerase chain reaction (PCR) detected mutation in FLT3-internal tandem duplication (ITD) and NPM1. This patient was treated with AML protocol but succumbed due to sepsis. This case highlighted the importance of recognising this clinicopathological presentations to provide rapid diagnosis and guide for the appropriate molecular testing. In this study, new treatment modalities available for this type of AML and literature review of previous studies were also discussed.